Consumer Decision Making Styles in Shopping Behavior Among Students: A Study Between Gender - Nur Haslina, Ramli (2010)
The general purpose of this study was to investigate the decision making style of Malaysian consumer on shopping behavior. The specific aim of this study is to investigate the different approach of male and female Malaysian consumer towards shopping behavior. The researcher used Sproles and Kendall's (1986) eight dimensions of Consumer Style Inventory (CSI) on a sample of 140 local undergraduate Malaysian's male and female students. For this purpose, structural questionnaires were used to gather information which could provide the answers to subject matter. The finding of this study showed that there is a significant difference between male and female consumers on brand conscious, price conscious and impulsive conscious shopping behavior. On the other hand, there is no significant difference between male and female consumers on high quality conscious, novelty fashion conscious, recreational conscious, confuse by over choice and brand loyal conscious shopping behavior. Recommendation, implication and direction for future research are also discussed.